Hypervelocity impacts into porous graphite: experiments and simulations. (28th January 2017) - Hébert, D.; Seisson, G.; Rullier, J.-L.; Bertron, I.; Hallo, L.; Chevalier, J.-M.; Thessieux, C.; Guillet, F.; Boustie, M.; Berthe, L.
Abstract : We present experiments and numerical simulations of hypervelocity impacts of 0.5 mm steel spheres into graphite, for velocities ranging between 1100 and 4500 m s −1 . Experiments have evidenced that, after a particular striking velocity, depth of penetration no longer increases but decreases. Moreover, the projectile is observed to be trapped below the crater surface. Using numerical simulations, we show how this experimental result can be related to both materials, yield strength. A Johnson–Cook model is developed for the steel projectile, based on the literature data. A simple model is proposed for the graphite yield strength, including a piecewise pressure dependence of the Drucker–Prager form, which coefficients have been chosen to reproduce the projectile penetration depth. Comparisons between experiments and simulations are presented and discussed. The damage properties of both materials are also considered, by using a threshold on the first principal stress as a tensile failure criterion. An additional compressive failure model is also used for graphite when the equivalent strain reaches a maximum value. We show that the experimental crater diameter is directly related to the graphite spall strength. Uncertainties on the target yield stress and failure strength are estimated. This article is part of the themed issue 'Experimental testing and modelling of brittle materials at high strain rates'.